Laboratory study on reattachment of vertical root fractures using 4-META/MMA-TBB resin - Li, Huiying; Wang, Tong; Fu, Jing; Guo, Jinghan; Fang, Zhimin; Pan, Keqing; Xu, Haiping (Frontiers in Dental Medicine, 2025)
BackgroundReattachment of root fragments with appropriate adhesive materials is expected to be the last conservative treatment for preserving teeth with vertical root fractures (VRFs).ObjectiveThis study evaluated the biocompatibility of 4-META/MMA-TBB resin for root repair, compared with iRoot BP Plus, Fuji IX GIC, and Clearfil SA Luting. Fracture resistance and microleakage of the reattached roots were also tested.MethodsThe biocompatibility of set materials was evaluated on L929 fibroblasts. Cell Counting Kit-8 (CCK-8) assay, live/dead cells staining and flow cytometry were used to assess cell biocompatibility. VRFs were created in bovine teeth, which were then reattached with set materials (excluding iRoot BP Plus). For the fracture resistance test, the roots were vertically fractured through the root canals (n = 20). The fracture resistance was compared with sound roots (control group) and fracture patterns were observed under a microscope. Microleakage was also tested on the reattached roots (n = 10). Results were analyzed by one-way ANOVA and the Tukey test. The significance level was set at α = 0.05.ResultsClearfil SA Luting group exhibited the highest cytotoxicity. The other test materials had acceptable cytotoxicity, not exceeding Grade 1 [relative growth ratio (RGR) > 75%] in CCK-8. Flow cytometry showed that the proportion of viable cells exposed to 4-META/MMA-TBB resin displayed no significant difference compared with iRoot BP Plus (P > 0.05). The root fracture resistances reattached using 4-META/MMA-TBB resin and Clearfil SA Luting were higher than that by Fuji IX GIC, but lower than those of the control group (P < 0.05). The difference between the two resin groups was statistically insignificant (P > 0.05). As for the microleakage, 4-META/MMA-TBB resin group had the shortest penetration depth, whereas Fuji IX GIC group showed the longest penetration (P < 0.05).Conclusions4-META/MMA-TBB resin had acceptable cell biocompatibility for root repair, similar to iRoot BP Plus. It can provide good fracture resistance and excellent sealing effect for reattaching treatment of VRFs.